Attraction of fruit-eating bats with essential oils of fruits: A potential tool for forest restoration - Bianconi, Gledson V.; Mikich, Sandra B.; Teixeira, Sirlei D.; Maia, Beatriz Helena L. N. S. (Blackwell Publishing, 2007)
Previous tests with essential oils from ripe chiropterochoric fruits suggested they can be used to attract and capture fruit-eating bats inside forest remnants. Here we evaluated the efficiency of these oils to attract frugivorous bats to open areas. We performed field tests with artificial fruits impregnated with essential oils of the genera Piper or Ficus that were attached to two groups of mist-nets set 50 m outside the border of a forest remnant. One group of artificial fruits received the corresponding oil isolated through hydrodistillation and the other received water only. Fruits with oils attracted significantly more fruit-eating bats, especially Artibeus lituratus that regularly crosses open habitats to reach other forest remnants. The highly significant attraction of A. lituratus by the oil of Piper was unexpected, since this bat is a specialist on Ficus fruits. We hypothesize that in habitats with no fruit available it is possible to attract frugivorous bats with the odor of several ripe fruit species. Furthermore, we verified that almost half of the individuals captured defecated seeds, indicating that the oils also attract recently fed bats, even when their preferred food is available nearby. This technique potentially may increase seed rain at specific locations, being particularly promising to restoration projects.
Keywords: Atlantic forest; conservation biology; Ficus; forest regeneration; frugivory; fruit bats; Phyllostomidae; Piper; restoration ecology; seed dispersal